Is there a correlation between sensory impairments and social isolation in middle-aged and older Chinese population? Cross-sectional and longitudinal evidence from a nationally representative survey - Ye Liu; Ye Liu; Ye Liu; Qinglei Sun; KaiweiSa Abuduxukuer; KaiweiSa Abuduxukuer; KaiweiSa Abuduxukuer; Yanan Hou; Yanan Hou; Jin Wei; Jin Wei; Haiyun Liu; et al. (Frontiers Media S.A., 2023)
PurposeThe aim of this study is to investigate the cross-sectional and longitudinal associations between sensory impairments (SIs) including single vision impairment (SVI), single hearing impairment (SHI), and dual sensory impairments (DSI) with social isolation in the middle-aged and older Chinese population.MethodsData were obtained from the China Health and Retirement Longitudinal Survey (CHARLS). In total, 11,674 Chinese older adults aged over 45 were included at baseline 2011, and 6,859 participants who accomplished all four interviews from 2011 to 2018 were adapted for longitudinal analyses. Sensory status and social isolation measurements including social disconnectedness and self-perceived loneliness were collected. Assessment of social disconnectedness included the number of types of social activities in which they participated and the frequency of such participation. Loneliness referred to the subjective perception of loneliness. Other covariates included socio-demographic characteristics, medical conditions, and lifestyle-related factors. The impacts of baseline sensory status on social disconnectedness and loneliness were assessed using univariate and multivariate generalized linear models. A generalized linear model with generalized estimation equations (GEE) was used to assess the association between time-varying sensory statuses with social disconnectedness or loneliness over 8 years after being adjusted with multi-confounding factors.ResultsParticipants with SIs had significantly higher levels of social disconnectedness and self-perceived loneliness, compared to those who were free of SI. All kinds of SIs were significantly associated with loneliness according to both cross-sectional and longitudinal data. The correlations between DSI and social disconnectedness or loneliness at baseline and over 8 years were also noticed. SHI was found to be significantly associated with both frequency and types of social activities according to cross-sectional data and with the frequency of social activity participation in longitudinal analysis. SVI was only associated with the types of social activities at baseline (all p-values < 0.05).ConclusionSensory impairments, especially dual sensory impairments, have explicitly detrimental effects on social isolation among the older Chinese population. Over time, single hearing impairment specifically jeopardizes their frequency rather than types of social activities participation.